Waqf Management from the Perspective of K.H. Abdul Manaf Mukhayyar for Islamic Education Development at Darunnajah Jakarta - Manaf, Sofwan (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
This study examines the role of waqf management according to K.H. Abdul Manaf Mukhayyar in the development of Islamic education at the Darunnajah Islamic boarding school in Jakarta. The main focus of this study is to identify the views of KH. Abdul Manaf Mukhayyar and the implementation of waqf management in the development of Islamic education at the Darunnajah Islamic boarding school. The method used in this study was descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study show that, according to K.H. Abdul Manaf Mukhayyar, waqf management is the key to the independence of Islamic boarding schools because waqf must be positioned as the main source of education funding that is free from personal interests. He emphasized the importance of separating personal assets and waqf assets, transparency in management, and accountability through layered evaluation. Implementation at Darunnajah includes the management of land assets, buildings, cash funds, and productive business units, with a routine evaluation system involving the nadzir council, foundation administrators, and a financial audit team. The impact of the implementation of waqf management is felt directly by students, teachers, and employees through education subsidies, scholarships, and the expansion of Islamic boarding school branches. Thus, K.H. Abdul Manaf Mukhayyar's views and application of waqf management have proven to play an important role in maintaining accountability, increasing public trust, and strengthening the independence of Islamic educational institutions. The waqf management model that he initiated and implemented at the Darunnajah Islamic Boarding School can be used as an example for other Islamic educational institutions in realizing an independent, sustainable, and community-oriented education system.